Predictors of Suicidal Ideation in Late Childhood and Adolescence: A 5‐Year Follow‐Up of Two Nationally Representative Cohorts in the Republic of Korea. Issue 1 (28th January 2013) - Park, Sunhee
<x xml:space="preserve">Abstract</x> This study explores the trajectory of suicidal ideation in childhood and adolescence and identifies its strong predictors. Secondary data obtained from two nationally representative cohorts of South Korean youth were longitudinally analyzed using frequencies, percentages, and discrete time survival analysis. This study revealed an increase in the occurrence of suicidal ideation in adolescence, a higher prevalence of suicidal ideation among females than among males, and differences in predictors of suicide ideation by developmental stages and gender. The results suggest that multifaceted factors specific to developmental stages and gender should be simultaneously considered to diminish the occurrences of suicidal ideation.